Investigations of the Site of the Ancient Town of Kalos Limen. Archaeological Survey of 2019 and Excavations of 2021–2022 - Eremeeva, Anna (Hyperboreus, 2024)
In 2019, the archaeological mission of the State Hermitage Museum carried out an extensive archaeological survey on the site of the ancient town of Kalos Limen and on its necropolis and chora. As a result of the survey, excavations were conducted at Kalos Limen during the seasons of 2021–2022. These excavations led to the discovery of a large residential complex, which existed with some modifications from the early 4th century BC to the first third of the 3rd century BC. The residential structure was destroyed in the first third of the 3rd century BC, which should be associated with the nomads’ attack at the chora of Chersonesos. The ruins of the residential structure apparently have never been restored. Partly it was turned into a dump in antiquity.